Borderline Clear Cell Adenofibroma of the Ovary. (30th March 2017) - Kleebkaow, Pilaiwan; Aue-aungkul, Apiwat; Temtanakitpaisan, Amornrat; Kietpeerakool, Chumnan
Abstract : Borderline clear cell tumors are extremely rare, and few cases have been reported in the literature. Herein, we present a case of borderline clear cell adenofibroma of the ovary in a 58-year-old woman who presented with a pelvic mass and constipation. Physical examination revealed a 10 cm solid midline pelvic mass. Computed tomography showed an 8 cm heterogeneous enhancing mass attached to the left posterolateral wall of the uterus. The patient's serum CA 125 levels were slightly elevated (80.9 U/ml). The patient was given a total abdominal hysterectomy with bilateral salpingooophorectomy. On gross examination, it was found that the left ovarian tumor was an 8.0 × 7.5 × 8.0 cm solid multilobulated mass containing tiny cysts. Histologically, the tumor was composed of small glands in dense fibrous and myxoid stroma. The glands were lined with cuboidal cells with clear cytoplasm and mild to moderate nuclear atypia. No stromal invasion was observed. The pathological diagnosis was borderline clear cell adenofibroma of the left ovary. There was no reoccurrence 36 months post operation.